THE INFLUENCE SEED TREAMENT OF BIOLOGICAL PRODUCTS ON INDICATORS OF THE STRUCTURE HARVEST AND YIELD PEA VARIETIES - Чинчик, О. С. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
The aim of research was to study the characteristics of structure formation crop varieties mustache pea morphotypes by biological agents for seed treatment. Analyzing samples sheaves four varieties of peas, determine the total number of stems in bundles; the number of productive stems in bundles; the number of unproductive stems in bundles; the average number of pods per plant, analyzing 25 plants; the average number of grains, 1000 grain weight and the average weight of a grain of beans on the same 25 plants. It was found that in the southern part of the western forest-steppe on the productivity performance of individual grain varieties of field-growth peas had the greatest impact Rhizobofit seed treatment, Fosfoenteryn and Biopolitsyd. In our studies the use Rhizobofit seed treatment, Fosfoenteryn and Biopolitsyd was increased the germination of pea seeds. Integrated use of all three biologics increased the germination rate of 1-1.5%. Maximizes field germination of these drugs in grades Chekbek. Survival pea plants depended on the varieties and fertilizers characteristics. The greatest number of plants before the harvest was in grade Chekbek - 1142.3 thousand/ha, and the survival percentage - for seed treatment Rhizobofit, Fosfoenteryn and Biopolitsyd. The maximum height of the plants was in grade Ulus in processing Rhizobofit, Fosfoenteryn and Biopolitsyd. At the same use case produces a variety of biological products Otaman largest number of beans, seeds and seed weight per plant, and the maximum weight of 1000 seeds formed Chekbek grade. The highest yield in the experiment provide seed treatment Rhizobofit, Fosfoenteryn and Biopolitsyd. Thus, the yield was 3.91 Tsarevych varieties t/ha, or 0.28 t/ha more than in the control variant. Maximum productivity at the same seed treatment was pea varieties Chekbek and Otaman and amounted to 4.11 and 4.10 t/ha.